SISTEM PERTANGGUNGJAWABAN DIREKSI DALAM HOLDING COMPANY - ABDUL AZIS ALSA; BISMAR NASUTION; WINDHA WINDHA (TRANSPARENCY, 2013)
A limited liability company be an option that is often used for a variety of business economy, also greatly influences the national economy. Holding company is a structure of legal connected each and others composing an economic unity that submit to a director of holding company and subdiary. Writing method used to compile this paper is the normative legal research or library research, by collecting material from books, magazines, papers, internet, legislation and other scholarly writings which closely related with the intent and purpose of the preparation of this paper. The result of this paper it can be conclude that Arrangement on limited liability company still using Indonesian Law No.40 of 2007 also regulated in the law that regulates specifically about other matters relating to the corporation law, the Indonesian Law No.40 of 2007 still maintaining the recognition of juridical status of a legal entity's holding companies and subsidiaries as independent legal subject but does not give a juridical recognition of the ‘company grup’ as as a separate legal entity vis-à- vis other law agencies. Therefore have a Board of Directors' duties and responsibilities to the company and has been established in the legislation. Kata kunci :Sistem, Pertanggungjawaban Direksi, Holding Company.